James Joyce and the Exilic Imagination - Gillespie, Michael Patrick (Book collections on Project MUSE., 2015)
In this book, Michael Gillespie provides new readings of James Joyce's main oeuvre through the lens of exile studies, and, in doing so, challenges the tendency in Joyce criticism to give more weight to reading that stress his negative view of Ireland.